Budowanie przewagi konkurencyjnej oparte na zasobach niematerialnych w warunkach globalizacji - Głuszek, Ewa (Invisible assets in the competitive advantage building on global markets., 2005)
There are four fundamental kinds of competitive advantage successful companies build on global markets: natural advantage, price - quality advantage, solution supply advantage and barrier build advantage. Each of them needs different intangible resources and the way of using them in the value chain. These basic kinds of competitive advantage can be described by three criteria - visibility, importance and durability. The article shows what types of intangible assets are the most important in advantage building process.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (3); 2005; nr 1093, s. 51-64